Diversification of Rice-Based Cropping System for Improving System Productivity and Soil Health in Eastern Gangetic Plains of India - Bharati Upadhaya; Kaushal Kishor; Vipin Kumar; Navnit Kumar; Sanjay Kumar; Vinod Kumar Yadav; Randhir Kumar; Ahmed Gaber; Alison M. Laing; Marian Brestic; Akbar Hossain (Agronomy, 2022)
Mono-cropping in the farming system decline in farm profit, climate change, and food insecurity are some of the major concerns that lead to unsustainability in the agricultural production system in the Eastern Gangetic Plains. A study was conducted for three years from June 2019 to June 2022 at Dr. Rajendra Prasad Central Agricultural University, Pusa, Bihar, India, to assess the profitable and best rice-based cropping system through crop diversification for sustainable agriculture. Ten different cropping sequences were exploited using randomised block design and replicated thrice, with the system productivity ranging from 8.70 to 24.95 t ha−1 under the different cropping sequences. The system productivity was increased by 187% and profitability by 299.52% in the maize − Cole crops − sesame cropping system over the rice − wheat cropping system. A diversified cropping system with black gram − maize + vegetable pea − sesbania possessed significantly more soil organic carbon (0.49%), bacterial population (47.85 × 106 cfu/g soil), azotobacter population (42.96 × 104 cfu/g soil), phosphate solubilising bacteria (20.72 × 106 cfu/g soil), dehydrogenase activity (4.39 µg TPF/g/h), fluorescein diacetate hydrolytic activity (17.28 µg fluorescein/g/h) and acid phosphatase activity (451.46 µg pNP/g/h), as well as urease activity (47.21 µg NH4+/g/h), relative to the rice–wheat cropping system. Therefore, the adoption of vegetables and legumes as diversified crops are viable options for enhancing productivity, profitability and soil health in the EGPs.